Aquinas Academy 1945-2015. - Thorpe, Julie (ATF Press, 2016)
This book tells the stories of women and men of the Aquinas Academy, a centre of adult education in Sydney founded in 1945 by an Australian Marist priest, Austin Woodbury. The book places the personal narratives within the social, cultural and intellectual landscape of Australian Catholicism spanning seven decades. Chapters trace the founding vision of the academy as a Catholic institution of higher education affiliated with Saint Thomas Aquinas's university in Rome, the expansion of programmes of adult spirituality across the eastern Australian states and the growing place of contemplative an.